An algorithmic foldover procedure for nearly orthogonal arrays with projection. (1st January 2011) - Haase, Casey L.; Hill, Raymond R.
Nearly orthogonal arrays are a class of experimental designs that are useful for accommodating multiple mixed-level factors and small run sizes for factor screening experiments. Several algorithmic approaches have been used to construct such arrays using D, A, ave ( S 2 ), and most interestingly, projection properties to evaluate and classify candidate arrays. Nearly orthogonal arrays constructed to contain good projection properties make it possible to estimate higher order interactions for subsets of design columns but can introduce significant correlation as to make some factor estimates terribly imprecise. This paper proposes a method to exploit the projection properties of these nearly orthogonal arrays while guarding against correlated factor effects. The usefulness of this foldover technique is demonstrated by a live-virtualconstructive simulation experiment.